x + 2 x 2 + 7 x + x + 7 = 3 5 − 2 x
The real solution to the above equation is of the form b a , where a and b are positive coprime integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Cj Lagmay Nice question! I think it might work better if it were not multiple-choice, since right now people can just plug the given options in to see if they satisfy the equation rather than actually solve the equation for x . If the final question was something like "If x = b a where a , b are positive coprime integers, then find a + b ", then the question would be more challenging and would better test factoring skills. If you think this is a good idea, just let me know and we can ask staff to make that change. :)
sorry too... i'm just new here and my tablet is not on it's best condition... It's a really detailed solution too... thanks Brian!!
Log in to reply
Thanks! I'll ask staff to change it from multiple-choice to standard form then.
@Calvin Lin I think this question would work better if it were not multiple-choice, but instead went something like "If x = b a where a , b are positive coprime integers, then find a + b ", with the standard format answer then being 9 8 5 . See what you think. Thanks.
Problem Loading...
Note Loading...
Set Loading...
First note that ( x + x + 7 ) 2 = x + 2 x 2 + 7 x + x + 7 = 2 x + 7 + 2 x 2 + 7 x .
So 2 x 2 + 7 x = ( x + x + 7 ) 2 − ( 2 x + 7 ) .
Substituting this into the given equation gives us that
x + ( ( x + x + 7 ) 2 − ( 2 x + 7 ) ) + x + 7 = 3 5 − 2 x ⟹
( x + x + 7 ) + ( x + x + 7 ) 2 = 3 5 − 2 x + ( 2 x + 7 ) = 4 2 .
Now let y = x + x + 7 . This last equation can then be written as
y + y 2 = 4 2 ⟹ y 2 + y − 4 2 = 0 ⟹ ( y + 7 ) ( y − 6 ) = 0 .
Now as y involves the sum of two square roots we know that y ≥ 0 , so we choose the positive root y = 6 , and so x + x + 7 = 6 . Squaring both sides yields
x + 2 x 2 + 7 x + x + 7 = 3 6 ⟹ 2 x 2 + 7 x = 2 9 − 2 x .
Squaring both sides yet again gives us that
4 ( x 2 + 7 x ) = 2 9 2 − 1 1 6 x + 4 x 2 ⟹ 2 8 x + 1 1 6 x = 8 4 1 ⟹ x = 1 4 4 8 4 1 = ( 1 2 2 9 ) 2 .
Thus a + b = 8 4 1 + 1 4 4 = 9 8 5 .
It can be checked that this value of x does indeed satisfy the original equation. Also, we know that it is the only real solution since the expression on the left of the original equation is a continuously increasing function starting at ( 0 , 7 ) , and the expression on the right is a continuously decreasing function intersecting the y-axis at ( 0 , 3 5 ) and the x-axis at ( 2 3 5 , 0 ) .